Digitalization of Marketing of Laskar Pelangi Local Agricultural Products - Hardianti, Hardianti; Nurmayanti, Nurmayanti; Lubis, Sandi; Sundari, Sundari; N, Zulkifli; Angareani, Reni (Journal La Lifesci, 2023)
The aim of this service is 1) increasing partners' knowledge about online sales and marketing strategies, 2) increasing partners' skills to produce quality and sustainable products. The partner in the service is the Laskar Pelangi agricultural group in Pattondon Salu. The method used in solving milking problems to achieve the goal is conducting in-depth interviews with partners and providing workshops and direct assistance as an effort to increase the income of Laskar Pelangi group members. From the results of this study, it was found that the fundamental key to achieving previously set goals is management. This management includes monitoring product quality, production scheduling, order management, as well as pricing and promotion strategies